2018
DOI: 10.3201/eid2402.171351
|View full text |Cite
|
Sign up to set email alerts
|

Emergomyces africanus in Soil, South Africa

Abstract: We detected Emergomyces africanus, a thermally dimorphic fungus that causes an HIV-associated systemic mycosis, by PCR in 18 (30%) of 60 soil samples from a wide range of habitats in South Africa. Direct and indirect culture techniques were unsuccessful. Experimental intraperitoneal inoculation of conidia induced murine disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 10 publications
0
25
0
Order By: Relevance
“…An ecologic niche has only been investigated for Es. africanus , which has been detected from various soil habitats and in air samples from Cape Town, South Africa ( 14 , 15 ). Further investigations are required to better understand the epidemiology and prevalence of disease caused by Emergomyces spp.…”
Section: Discussionmentioning
confidence: 99%
“…An ecologic niche has only been investigated for Es. africanus , which has been detected from various soil habitats and in air samples from Cape Town, South Africa ( 14 , 15 ). Further investigations are required to better understand the epidemiology and prevalence of disease caused by Emergomyces spp.…”
Section: Discussionmentioning
confidence: 99%
“…Schwartz et al used a nested (conventional) PCR strategy and found Es . africanus in 30% of soil samples assessed [ 16 ]. The main advantage of the protocol presented here is the ability of qPCR to quantify the number of propagules present.…”
Section: Discussionmentioning
confidence: 99%
“…africanus is still being elucidated, although an environmental reservoir of the mycelial phase in the soil is supported by molecular detection of Es . africanus in 30% of soils sampled from the Western Cape [ 16 ]. Nonetheless, most patients diagnosed with emergomycosis do not report occupational or other frequent exposure to soil [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…These molds are probably endemic in sub-Saharan Africa, but their precise geographic repartition and natural ecology remain to be established. Environmental studies would be necessary to further investigate the natural ecology of these molds, as has been done recently for the emerging Emergomyces africanus ( 19 ).…”
Section: Discussionmentioning
confidence: 99%